Differences in occupation between ancestry subgroups of Asian birthplace groups in Australia. Issue 2 (19th April 2018) - De Alwis, Sheruni; Parr, Nick
Abstract: Asia‐born migrants form a majority of Australia's immigrants. Most of the larger Asian birthplace groups are ethnically heterogeneous. However, the literature on the occupations of migrants in Australia has tended to overlook the diversity within individual migrant groups. Using 2011 census data, this study details for the first time the significant variation in the occupational distributions between ancestry subgroups of the 10 largest Asian birthplace groups in Australia. A majority of the birthplace and ancestry groups have higher overall occupational status scores than the Australia‐born. The European and Australian ancestry subgroups are more likely to be managers, while the Chinese and Indian ancestry groups are more likely to be in particular professional occupations and to have higher overall occupational status than other ancestry groups from the same birthplace. In other ancestry subgroups such as Punjabi and Sikh ancestry India‐born, high proportions of migrants are in low‐skilled occupations, indicating wastage of skills.